2018
DOI: 10.1002/ghg.1772
|View full text |Cite
|
Sign up to set email alerts
|

Process analysis and economic evaluation of mixed aqueous ionic liquid and monoethanolamine (MEA) solvent for CO2 capture from a coke oven plant

Abstract: This study investigates the process and economic impacts of using an aqueous mixture of 1‐butylpyridinium tetrafluoroborate ([Bpy][BF4]) ionic liquid (IL) and monoethanolamine (MEA) as the solvent for CO2 capture from a coke‐oven plant. The gaps highlighted in the literature on the study of an aqueous mixture of IL and MEA for CO2 capture include lack of detailed process models or information on the impacts of varying the IL concentration on different process conditions and economics. This study addressed thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…At present, the absorption technology with 30 wt % MEA aqueous solution is the commercialized one. However, this technology with the corresponding solvent has the drawbacks of high energy demand (4.2 GJ/t CO 2 ), high cost ($0.19-1.31/t CO 2 ), low thermal and chemical stability, and high volatility and corrosion [3][4][5][6], which underlines the necessity for developing greener and more efficient solvent for CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the absorption technology with 30 wt % MEA aqueous solution is the commercialized one. However, this technology with the corresponding solvent has the drawbacks of high energy demand (4.2 GJ/t CO 2 ), high cost ($0.19-1.31/t CO 2 ), low thermal and chemical stability, and high volatility and corrosion [3][4][5][6], which underlines the necessity for developing greener and more efficient solvent for CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…A number of process simulation studies exist for assessing the performance of ILs and evaluating the cost of the overall CO 2 capture process as well as operating parameters such as the regeneration demands. Oko et al [99] compared a mixed aqueous solution of MEA and six different ILs, concluding that ILs based on the 2-cyanopyrrole anion showed the lowest circulation rate and lowest regeneration energy requirements. This energy was estimated at 3.6 GJ/t CO 2 by Zhai and Rubin [100].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…Regarding the solvent price, it was not possible to find reliable standard market prices as the solvent is not traded as a commodity. However, the price used is comparable to the reported for other solvents such as MEA [26]. The solvent cost is added to the capital cost, as it is not estimated in Hysys, and it is assumed that replacement of solvent is not necessary in the project lifetime, as it has been reported that DEPG is a stable solvent and is very resistant to degradation, even with oxygen [27] [28].…”
Section: Cost Estimationmentioning
confidence: 99%